IMPLEMENTASI PEMBANGUNAN JALAN LINGKUNGAN MASYARAKAT DALAM PENINGKATAN PELAYANAN PUBLIK PADA DINAS CIPTA KARYA DAN TATA KOTA SAMARINDA - Eddy Djunaidi (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
The result show that implementation of society road building in increasing public services at Dinas Cipta Karya & Tata Kota Samarinda has been conducting based on standart mechanism of development which prevailed and applied by the province government. The supporting factors are policy about the development authority, budgeting factor and a condusive work system. The barriers are lack of the people konwlegde and understanding about the contruction criteria used in society road building.